Carbon‐Intercalated 0D/2D Hybrid of Hematite Quantum Dots/Graphitic Carbon Nitride Nanosheets as Superior Catalyst for Advanced Oxidation. Issue 43 (18th September 2019) - Xi, Junhua; Xia, Hong; Ning, Xingming; Zhang, Zhen; Liu, Jia; Mu, Zijie; Zhang, Shouting; Du, Peiyao; Lu, Xiaoquan
Abstract: Efficient charge separation and sufficiently exposed active sites are important for light‐driving Fenton catalysts. 0D/2D hybrids, especially quantum dots (QDs)/nanosheets (NSs), offer a better opportunity for improving photo‐Fenton activity due to their high charge mobility and more catalytic sites, which is highly desirable but remains a great challenge. Herein, a 0D hematite quantum dots/2D ultrathin g‐C3 N4 nanosheets hybrid (Fe2 O3 QDs/g‐C3 N4 NS) is developed via a facile chemical reaction and subsequent low‐temperature calcination. As expected, the specially designed 0D/2D structure shows remarkable catalytic performance toward the removal of p ‐nitrophenol. By virtue of large surface area, adequate active sites, and strong interfacial coupling, the 0D Fe2 O3 QDs/2D g‐C3 N4 nanosheets establish efficient charge transport paths by local in‐plane carbon species, expediting the separation and transfer of electron/hole pairs. Simultaneously, highly efficient charge mobility can lead to continuous and fast Fe(III)/Fe(II) conversion, promoting a cooperative effect between the photocatalysis and chemical activation of H2 O2 . The developed carbon‐intercalated 0D/2D hybrid provides a new insight in developing heterogeneous catalysis for a large variety of photoelectronic applications, not limited in photo‐Fenton catalysis. Abstract : 0D hematite quantum dots/2D ultrathin g‐C3 N4 nanosheet hybrids are developed by simple chemical reactions and calcination. Highly exposed active surfaces, charge transfer at the intrinsic interface, and synergy between photocatalysis and H2 O2 lead to excellent catalytic performance for degrading p ‐nitrophenol. This work provides new insights into the development of heterogeneous catalysis for optoelectronic applications.